2020
DOI: 10.7759/cureus.7925
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and Renal Profile of Scrub Typhus Patients at a Tertiary Care Center in India

Abstract: Introduction Scrub typhus is a resurging zoonotic infection prevalent in South Asia with many recent outbreaks in India. It can mimic other tropical infections and the disease spectrum ranges from subclinical illness to life-threatening disease with multiorgan dysfunction. This study was conducted to study the pattern of hepatic and renal injury. Methods A retrospective study was done on 176 patients diagnosed by detecting IgM antibodies using an enzyme-linked immunosorbent assay (ELISA) over a period of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…A similar female majority has been reported in previous studies [7][8][9][10]. However, male preponderance also been reported in few studies [5,6,11].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar female majority has been reported in previous studies [7][8][9][10]. However, male preponderance also been reported in few studies [5,6,11].…”
Section: Discussionsupporting
confidence: 85%
“…Kumar et al [5] found that average age of the scrub typhus cases was found to be34.16. Gaba et al [6] reported that the mean age at the time of diagnosis of scrubtyphus cases was found to be 32.3±13. A study carried out in SriLanka [7] also found that the mean age of scrub typhus cases was reported as 34.6.…”
Section: Discussionmentioning
confidence: 99%
“…Higher female dominance is attributed to greater involvement of women in agricultural and outdoor activities [20] . A study in south India in Telangana also found that 24.1% of patients had a history of exposure to vegetation and agricultural works [5] . Similarly, about 34% of the current study participants were involved in agricultural activities.…”
Section: Discussionmentioning
confidence: 96%
“…It is an acute zoonotic infection caused by a mite-borne bacterium called Orientia tsutsugamushi, which is transmitted via insect bites [3] . The arthropod responsible for this transmission, which also serves as a reservoir for this bacterium, is the Leptotrombidium mite [4][5][6][7][8] . O. tsutsugamushi is a Gram negative, obligate, intracellular organism [4,7] .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for the deposition of O. tsutsugamushi in endothelial cells which is supported by positive immunohistochemistry for its antigen. Almost 30% of the individuals go on to develop one organ dysfunction if untreated and the most common being AKI or acute hepatic failure (AHF) [7,[11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%